ENTREPRENEURIAL BEHAVIOUR OF RURAL WOMEN INVOLVED IN HANDLOOM INDUSTRY OF ASSAM - DEEKSHITA DUTTA* and T. RADHA (The Journal of Research ANGRAU, 2022)
This study was conducted in the Lakhimpur district of Assam in August, 2021 with an objectiveto analyse the entrepreneurial behaviour of rural women involved in handloom industry. The researcherselected 25 women from two villages using random sampling method, thus, making a total samplesize of 50 respondents. The nine dimensions of entrepreneurial behaviour were studied to evaluatethe level of entrepreneurial behaviour i.e. innovativeness, achievement motivation, decision-makingability, risk-orientation, information-seeking behaviour, cosmopoliteness, self-confidence, economicmotivation and management orientation. The results revealed that more than half of the respondents(56%) had medium level of entrepreneurial behaviour, followed by respondents with low level ofentrepreneurial behaviour comprising of 28%. Only 16% of the respondents were found to have highlevel of entrepreneurial behaviour.